PELATIHAN PERENCANAAN KEUANGAN BAGI PETUGAS PARKIR KOTA MATARAM - Nina Karina Karim; Siti Atikah; Indria Puspitasari Lenap (Jurnal Abdimas Sangkabira, 2022)
Knowledge on how to plan domestic income will help parking attendants to manage their daily income which will enable them to provide their children’s education as well as other family needs. This training is intended to provide tips and ideas on how parking attendants listed in Mataram Municipality Transportation Services can manage their income that have recently been affected by the implementation of e-parking system. Participants of this training activity were given tutorials and counseling individually instead of groups in a classroom setting. As many as twenty parking attendants operating in business areas around Mataram and Cakranegara area were tutored on how to adjust to the new income pattern and were provided with booklets on financial planning. Information was also collected by means of questionaires to acquire deeper background on the parking attendants’ opinion on the implementation of the e-parking system.